Calculations with spectroscopic accuracy for energies, transition rates, hyperfine interaction constants, and Landé gJ-factors in nitrogen-like Kr XXX. (January 2017) - Wang, K.; Li, S.; Jönsson, P.; Fu, N.; Dang, W.; Guo, X.L.; Chen, C.Y.; Yan, J.; Chen, Z.B.; Si, R.
Abstract: Extensive self-consistent multi-configuration Dirac-Fock (MCDF) calculations and second-order many-body perturbation theory (MBPT) calculations are performed for the lowest 272 states belonging to the 2 s 2 2 p 3, 2 s 2 p 4, 2 p 5, 2 s 2 2 p 2 3 l, and 2 s 2 p 3 3 l ( l = s, p, d ) configurations of N-like Kr XXX. Complete and consistent data sets of level energies, wavelengths, line strengths, oscillator strengths, lifetimes, A J, B J hyperfine interaction constants, Landé g J -factors, and electric dipole (E1), magnetic dipole (M1), electric quadrupole (E2), magnetic quadrupole (M2) transition rates among all these levels are given. The present MCDF and MBPT results are compared with each other and with other available experimental and theoretical results. The mean relative difference between our two sets of level energies is only about 0.003% for these 272 levels. The accuracy of the present calculations are high enough to facilitate identification of many observed spectral lines. These accurate data can be served as benchmark for other calculations and can be useful for fusion plasma research and astrophysical applications. Abstract : Highlights: Energies, transition rates, hyperfine interaction constants, and Landé g J -factors for the lowest 272 levels in Kr XXX are reported. The MBPT and MCDF methods are employed. The most accurate and complete atomic data in Kr XXX are provided to date.